Making commissioning work: The relational gap between intent and implementation in the transition to 'commissioning' community services in New South Wales. Issue 3 (25th August 2021) - Riboldi, Mark; Fennis, Lisa; Fishwick, Elaine; Goodwin, Susan; Stears, Marc
Abstract: The question of impact is at the heart of human service design, with governments searching perennially for the right approach to meeting citizen need while responsibly acquitting public funds. In this area, 'commissioning' has become a popularised approach, most recently in Australia. Although in theory commissioning is a strategic and relational practice offering to put communities at the heart of decision‐making, commissioning in practice has proved less transformational. This paper explores the gulf between intent and implementation in the transition to commissioning human services in New South Wales (NSW) in the context of the Commissioning Project, a collaborative project facilitated by the Sydney Policy Lab at the University of Sydney to enable peak organisations in the community sector build a collective approach to commissioning. The collaboration resulted in the articulation of four guiding principles to facilitate better commissioning in NSW: putting relationships first, letting communities lead, investing in people, and embedding learning. Abstract : This paper describes a collaborative research project with a coalition of community sector peak organisations wanting to develop a collective response to the transition to commissioning human services in New South Wales. Through our experience, we identify four principles for better commissioning to address the identified gap between policy rhetoric and practice.